2001
DOI: 10.1073/pnas.061029298
|View full text |Cite|
|
Sign up to set email alerts
|

Complete genome sequence of Caulobacter crescentus

Abstract: The complete genome sequence of Caulobacter crescentus was determined to be 4,016,942 base pairs in a single circular chromosome encoding 3,767 genes. This organism, which grows in a dilute aquatic environment, coordinates the cell division cycle and multiple cell differentiation events. With the annotated genome sequence, a full description of the genetic network that controls bacterial differentiation, cell growth, and cell cycle progression is within reach. Two-component signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
449
1
38

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 496 publications
(496 citation statements)
references
References 39 publications
8
449
1
38
Order By: Relevance
“…The gene in which this insertion is located, designated "xylX" by Meisenzahl et al (18) and later "CC0823" in the C. crescentus genome annotation (19), does not closely resemble any gene of known function. xylX is the first gene in a xylose-inducible operon (CC0823-CC0819) (12), referred to here as the xyl operon.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The gene in which this insertion is located, designated "xylX" by Meisenzahl et al (18) and later "CC0823" in the C. crescentus genome annotation (19), does not closely resemble any gene of known function. xylX is the first gene in a xylose-inducible operon (CC0823-CC0819) (12), referred to here as the xyl operon.…”
mentioning
confidence: 99%
“…The xylA gene product was annotated by the C. crescentus genome project as a "short-chain aldehyde dehydrogenase," while the xylB product was annotated as an "oxidoreductase" (19). To determine whether XDH activity is attributable to one of these gene products, the PCR-amplified coding regions were cloned separately into the pCR-CT-T7-Topo expression vector to allow production of C-terminal His-tagged proteins in E. coli strain BL21( DE3) pLysS (Invitrogen).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant plasmids were used for automatic DNA sequencing with BigDye terminators on a ABI Prism 377 sequencer (AP Biosystems). The insertion site was determined by comparison to the complete C. crescentus genome sequence (19).…”
Section: Identification Of the Tn5 Insertion Sitesmentioning
confidence: 99%
“…crescentus is an aquatic bacterium belonging to the alpha subfamily of the proteobacteria, and no homolog of σ S was identified in the genome sequence (19), suggesting that the regulation of stationary phase genes could be carried out by a different system. A previous work showed that when in late stationary phase Caulobacter undergoes a morphological change and display increased resistance to stress (29).…”
Section: Introductionmentioning
confidence: 99%